Three phase fault algorithm in distribution system by using database approach and impedance based method - Shamsudin, N.H.; Latiff, A.A.; Abas, N.; Mokhlis, Hazlie; Awalin, L.J. (2012)
A three phase fault location algorithm using database and impedance based method is utilized in distribution system to locate fault which may occur in any possible fault sections and to optimize the switching operations to reduce the outage time affected by fault. The configuration of 132/11kV from actual distribution system in Malaysia with 38 nodes is modelled using the PSCAD/EMTDC software. This work attempt to combine fault section identification with impedance based method in order to address non-homogeneity of cables in distribution system. The result which is the fault location result is obtained through the complete process which involves the database formation acquired through the PSCAD/EMTDC software simulator and the fault location distance calculation carried out by the MATLAB software. The comparison is made through proposed algorithm with actual data acquired from the utility board. Final outcome of the proposed algorithm shows good approximation on fault location.